Pedagogical Innovations During COVID-19 Lockdowns: Learner (In)accessibility to Radio Lessons in Poorly Resourced African Countries - Godsend T Chimbi (Studies in Learning and Teaching, 2024)
The COVID-19 pandemic brought unprecedented challenges in education globally. This article explores how learners in poorly resourced African countries accessed education during national lockdowns, if at all. With schools closed, how could learners in households without electricity and computers continue learning? Policy makers saw radio school as the only alternative. This comparative qualitative study on learner (in)accessibility to radio lessons in poorly resourced African countries during COVID-19 lockdowns is informed by the social justice theory. Data were obtained from online media, primary and secondary sources to generate insights into how radio lessons were conducted in six selected African countries – South Africa, Zimbabwe, Kenya, South Sudan, Liberia, and Sierra Leone. Findings indicate that learner experiences with radio lessons were heterogeneous. Where lesson broadcasts started soon after school shutdowns, worthwhile learning experiences were observed. Where radio school was introduced late, learner uptake of this innovation was low. In countries ravaged by poverty and toxic leadership most poor families could not afford radios, making radio lessons a charade. Compared to their privileged peers, who engaged in digital online learning, learners from poor families lost irrecoverable learning time in 2020 and 2021 - perpetuating existing inequalities and scuttling the drive for social justice.